Statistical S For Strengths Of Joining PA Sheets Welded By Friction Stir Welding Process (University of Thi-Qar Journal for Engineering Sciences, 2017)
In this research, a study of strengths for PA (Nylon 6,6) sheets welded by FSW process is analyzed by Minitab-16 program. For this purpose a commercial PA sheets provided with dimension of 250× 150× 8 mm were used. An especial tool was designed with 16 mm diameter for the shoulder, while pin length and diameter were 7.8 and 4 mm respectively. The rotation speeds used were (2000, 1570, 1255, 994, and 780) rpm, and traverse speeds were (27, 42, and 62) mm/min.tensile and impact tests were done in order to evaluate mechanical behavior of material. For analysis the effect of the variables on strength of the joint, software program (Minitab 16) used to design plan for joint and show the effects of the variables by analysis them. It was found that welding strength increases with increasing rotational speed and decreases with traverse speed increase and the optimum properties were obtained when these speeds were 1570 rpm and 42 mm/min respectively.